Analisis Tolok Ukur Non Konstitusi dalam Pengujian Undang-Undang Terhadap Undang-Undang Dasar 1945 - . Baharudin (KEADILAN PROGRESIF, 2012)
This research study about Analysis Measuring Rod of Non Constitution In Examination Of Code To Constitution 1945, problems focus cover: rule condition and reason of non constitution can be made measuring rod in examination of code to Constitution 1945 at Lawcourt Constitution. Result of research of menunjukan that there are basis for idea enabling of usage of[is non constitution in decision, that is is: First, Lawcourt Constitution in testing Code obliged to dig values punish and sense of justice which live in society pursuant to UUD 1945 as highest elementary law and also Code as formulation of UUD 1945. Both, Praktik Lawcourt Constitution in former decision No. 27/PUUVII/2009, 16 June 2010 for example expressing "... as long as Code, product discipline institute state, and law and regulation arranging formal or mechanism of prosedural that emit a stream of from delegation of kewenangan according to constitution hence that law and regulation can be utilized or considered as measuring rod or acid test in examination of formal". Third, Usage of other Code as base consideration of law exactly to create fair rule of law as determined in Section 28D sentence (1) UUD 1945, and is Fourth, Enjoinment use other Code as base consideration of law [is] to reduce Lawcourt kewenangan as judicial power which independence to carry out jurisdiction utilize to uphold justice and law, and if section of a quo applied hence will limit Lawcourt function and duty in executing kewenangan given by UUD 1945.